Factors Affecting Investment Decisions of Permanent School Teachers in Pokhara - Subedi, Yubaraj (Journal of Interdisciplinary Studies, 2023)
Investing is the use of money to increase its worth or generate more revenue. This article has been designed to examine the factors affecting investment decision of permanent school teachers in Pokhara. This study is based on causal comparative research design. It has used structured questionnaire to collect information. Samples were selected by multi sampling technique, selecting the than Chhorepatan Resource Center by purposive sampling in the first and selecting 139 permanent school teachers by simple random sampling in the second stage. The Total population of permanent school teachers of Pokhara Metropolitan City was 1,588 and targeted population was 211. The reliability of data is checked by calculating Cronbach Alpha and it was 0.77. Accounting information (AI), Firm`s Image (FI), Advocate Recommendation (AR), Personal Financial Need (PFA) and Dividend Policy (DP) were independent variable and Investment Decision (ID) was dependent variable. This research discovered that 61.2% of permanent teachers invest their fund in equity share. Lump sum investment method was more popular than systematic investment plan and monthly investment. 80% of permanent teachers invest less than 20% of their savings. Respondents prefers both cash and stock dividend policy. Regular income was found as main objective of investment. Friends and coworker’s advice was also considering while investing in equity share. This research has also presumed that there was positive significant relation between investment decisions and decision factors. It is suggested to the investors of stock market, to analyze the fundamental factors of issuer and the issuer should follow regular dividend policy to attract the value investors toward their securities.